Productos y atractivos turísticos de la parroquia pasa cantón Ambato, provincia de Tungurahua - Mantilla Martínez, Cristina de los Ángeles (2023)
The province of Tungurahua has shown significant tourism growth, however, not all cantons and parishes are of this growth and development; this was identified in the parish of Pasa, where there is no inventory of tourist attractions and products, with poor management and limited promotion and dissemination of them. Therefore, this project focuses on proposing strategies based on the parish's tourism resources. To achieve this, a review of primary and secondary sources was carried out, such as the Development and Land Use Plan of the parish, the cadastre of the Department of Culture and Tourism, in which it was found that 2 attractions were inventoried, so it was necessary to use the inventory cards of the MINTUR to make the inventory, obtaining a total of 9 attractions (5 natural and 4 cultural), For the inventory of a tourism product, the PROMPERÚ Tourism Product Planning Manual was used to analyze the destination, the demand and supply of the existing product, which is the tourist route "Vive y Siente Pasa un encanto por conocer", which is a full day tour and includes natural and cultural attractions in the nearby communities. Finally, a SWOT analysis was conducted, consisting of an analysis of external factors (MEFE), where it was determined that there is an influx of visitors, but they do not stay at the destination, they only go for a day or hours, the analysis of internal factors (MEFI) which highlights the realization of fairs of enterprises with local products, and the existence of a tourist information center, which does not have the staff for optimal operation. Strategies and an evaluation of the same were carried out, highlighting the management of tourist spaces in order to promote the attractions and tourist products in the most populated urban areas that allow the spread of tourism in the parish and attract the presence of more visitors to the sector. It can be concluded that the parish has resources and attractions to develop tourism, even so, it has several limitations; therefore, it is important to conduct more studies to define new products and create marketing, promotion and dissemination plans in other scenarios that promote the parish as a place for tourism, leisure and recreation activities.